Model of nitrogen-phosphorus ratio and phytoplankton relationship in lake Laut Tawar, Indonesia - Saiful Adhar; Munawwar Khalil; Erlangga Erlangga; Muliani Muliani; Rachmawati Rusydi; Mainisa Mainisa; Imanullah Imanullah; Yudho Andika (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Phytoplankton blooms in the lake cause ecological, economic, health, energy, and aesthetic losses. It reduces water quality and biota diversity, creates toxins in the waters, and changes the structures and functions of the ecosystem. The essential nutrients for the growth of phytoplankton are nitrogen and phosphorus. Controlling phytoplankton growth can be managed by controlling the limiting nutrient input. This study aims to identify the limiting nutrient, analyze variations in TN:TP ratio spatially and temporally, and model TN:TP ratio and chlorophyll-a relationship. This study used secondary data from previous studies, namely TN, TP, and chlorophyll-a observed monthly in seven stations purposively during a year. Rainfall data was also obtained from the previous study. Limiting nutrients were determined by Redfield theory, and data were analyzed by Spearman correlation, One-way ANOVA, Kruskal-Wallis, and regression analysis. The results showed phosphorus was a limiting nutrient for phytoplankton growth in Lake Laut Tawar. TN:TP ratio and chlorophyll-a did not vary spatially, indicating the lake surface waters were evenly mixed. The parameters varied temporally, expressing the influence of hydroclimatological factors, especially rainfall. Rainfall increases nutrient input to the lake, but only rain below 200 mm/month causes an increase in the concentration of nutrients in the lake. The rainfall above 200 mm/month increases lake water volume significantly, thereby reducing nutrient concentrations. TN:TP ratio and chlorophyll-a related negatively and formed a non-linear relationship with an empirical model Chlorophyll-a = 2770.285 (TN/TP)-1.871. Eutrophication of Lake Laut Tawar should be anticipated by controlling the anthropogenic phosphorus input.Keywords:AnthropogenicChlorophyll-aEutrophication,Limiting nutrientRainfall